Pengaruh Permainan Ular Tangga Terhadap Kecerdasan Logika Matematika Anak Kelompok B RA IP Qurrota A yun Ngrandu Kab. Sragen Tahun Ajaran 2015/2016 - Safitri, Safitri, Dr. Darsinah, MSi (2016)
The purpose of this research is to know the influence of the snake game ladders against the intelligence of the mathematical logic Group B at RA IP Qurrota A'yun Ngrandu Kab. Sragen academic year 2015/2016. This research is a research experiment with design research One-Group Pretest-Postest design. The subject of this research is the learners Group B at RA IP Qurrota A'yun Ngrandu Kab.Sragen academic year 2015/2016. Data on children's mathematical logic intelligence gathered through observation and documentation. Data analysis technique used is the t-test. The results of the data analysis the value tcount-49.598 ≤-ttable-1.771 then Ho denied and Ha is received. Thus it can be concluded that the snake game ladder effect on intelligence of mathematical logic Group B RA IP Qurrota A'yun Ngrandu Kab. Sragen academic year 2015/2016.